2019
DOI: 10.3390/nu11051178
|View full text |Cite
|
Sign up to set email alerts
|

May Young Elite Cyclists Have Less Efficient Bone Metabolism?

Abstract: The purpose of this work was to describe changes in metabolic activity in the bones of young male competitive cyclists (CYC) as compared with age-matched controls (CON) over a one-year period of study. Eight adolescent male cyclists aged between fourteen and twenty, and eight age-matched controls participated in this longitudinal study. Serum osteocalcin (OC), amino-terminal propeptide of type I procollagen (PINP), beta-isomerized C-telopeptides (β-CTx) and plasma 25 hydroxyvitamin D [25(OH)D], were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Although a large number of studies have confirmed the lack of positive effects of these endurance activities on BMD and BMC levels in adolescents, there is not much direct and strong evidence regarding the related BTM indicators. The research results of Rapun-Lopez et al [ 56 ] showed that, with increasing age, OCN and PINP concentrations decreased in both the cycling group and the control group, while β-CTX concentrations showed no significant difference. However, it should be pointed out that, during this period, the vitamin D level of the cyclists decreased significantly.…”
Section: Endurance Exercise and Bonementioning
confidence: 99%
“…Although a large number of studies have confirmed the lack of positive effects of these endurance activities on BMD and BMC levels in adolescents, there is not much direct and strong evidence regarding the related BTM indicators. The research results of Rapun-Lopez et al [ 56 ] showed that, with increasing age, OCN and PINP concentrations decreased in both the cycling group and the control group, while β-CTX concentrations showed no significant difference. However, it should be pointed out that, during this period, the vitamin D level of the cyclists decreased significantly.…”
Section: Endurance Exercise and Bonementioning
confidence: 99%
“…Two other studies investigated the links between 25(OH)D and bone outcomes in young populations. Gil-Cosano et al [4] revealed a mediating effect of muscular fitness on the relationship between 25(OH)D levels and BMD in children who were overweight/obese, while Rapun-Lopez et al [5] showed similar bone remodeling in adolescent male cyclists than age-matched active controls over one year, but lower 25(OH)D. In adult and older women from the Chilean National Health Survey 2016-2017 (total N = 1931), Solis-Urra et al [6] found a joint association of high sedentary time/passive commuting to be associated with 25(OH)D deficiency, even after controlling for sun exposure. This finding connects with the studies mentioned above [1][2][3] due to the proposed link between sedentary time and increased adiposity, as well as between adiposity and reduced 25(OH)D levels.…”
mentioning
confidence: 99%